Head-to-head intra-individual comparison of biodistribution and tumor uptake of (18F)FAPI-74 with (18F)FDG in patients with PDAC: a prospective exploratory study - Novruzov, Emil; Giesel, Frederik L.; Mori, Yuriko; Choyke, Peter L.; Dabir, Mardjan; Mamlins, Eduards; Schmitt, Dominik; Antke, Christina; Pinto, Claudio; Soza-Ried, Cristian; Fernandez, Rene; Amaral, Horacio; et al. (Cancers, 2023)
Background: Radiolabeled fibroblast activation protein (FAP) ligands, a novel class of tracers for PET/CT imaging, have demonstrated very promising results in various oncological, as well as in some benign, diseases with long-term potential to supplant the current pan-cancer agent [18F]FDG in some cancer types. Pancreatic ductal carcinoma (PDAC) belongs to the group of epithelial malignancies with a strong so-called “desmoplastic reaction”, leading to a prominent tumor stroma with cancer-associated fibroblasts that exhibit a marked overexpression of fibroblast activation protein (FAP). The first clinical experiences in PDAC with 68Ga-labeled FAP ligands suggested superior sensitivity to [18F]FDG. However, there is limited data with 18F-labeled FAP derivatives, i.e. [18F]FAPI-74, yet prospective single- and multicenter trials are already ongoing. In this proof-of-concept study, we sought to evaluate the biodistribution, tumor uptake, and lesion detectability in patients with PDAC using [18F]FAPI-74 PET/CT as compared to [18F]FDG PET/CT scans for staging. Methods: This study includes 7 patients (median age 69) who underwent both [18F]FDG PET/CT with contrast-enhancement and [18F]FAPI-74 PET with low-dose CT for primary staging (n = 3) and therapy response control after neoadjuvant (n = 1) or re-staging after palliative therapy (n = 3). The mean interval between PET scans was 11 ± 4 days (range 1-15 days). The [18F]FDG and [18F]FAPI-74 PET/CT scans were acquired at 64 ± 4.1 min (range 61-91 min) and 66.4 ± 6.3 min (range 60-76 min), respectively, after administration of 200 ± 94 MBq (range 79-318 MBq) and 235 ± 88 MBq (range 90-321 MBq), respectively. Quantification of tracer uptake was determined with SUVmax and SUVmean. Furthermore, the tumor-to-background ratio (TBR) was derived by dividing the SUVmax of tumor lesions by the SUVmax of adipose tissue, skeletal muscle, and blood pool. Results: Overall, 32 lesions were detected in 7 patients including primary (n = 7), lung (n = 7), bone (n = 3), lymph node (n = 13), and peritoneal metastases (n = 2). [18F]FAPI-74 detected 22% more lesions compared with [18F]FDG with a better TBR and visual lesion delineation. In one patient the primary lesion could be detected unequivocally with [18F]FAPI-74 but was missed by [18F]FDG imaging. Altogether, most of the lesions demonstrated markedly elevated uptake of [18F]FAPI-74 with a simultaneous lower uptake in the background, providing a very high visual contrast. Conclusion: To the best of our knowledge, this is the first, prospective, intra-individual investigation comparing [18F]FAPI-74 with [18F]FDG imaging in PDAC with encouraging results. These pivotalresults supporta larger, multicentric, prospective study to determine the value of [18F]FAPI-74 in detecting and staging PDAC in comparison with current standard of care imaging.
Veröffentlicht: 17. Mai 2023
Gesehen am 26.07.2023
Im Titel ist der Ausdruck "18F" eckig geklammert und die Zahl 18 hochgestellt